(untitled) (Salud, Arte y Cuidado, 2026)
This study identifies the actions implemented by the nursing departments and schools of federal public universities in Brazil to support health workers in facing the COVID-19 pandemic. A documentary analysis was conducted based on data obtained from social networks and the websites of the nursing departments and schools of five public universities: the Federal University of Santa Catarina, the Federal University of São Paulo, the University of Brasília, the Federal University of Amazonas, and the Federal University of Ceará. The content was analyzed using Bardin’s Content Analysis technique. Several action fronts were established to design and implement initiatives aimed at the university community, health professionals, and society, encompassing managerial, educational, and assistance measures. The nursing departments and schools of Brazilian public universities have developed initiatives aligned with frontline professionals, providing scientific support for safe and effective action during the pandemic.